Faktoren fur̈ die Zufriedenheit mit Qualitaẗssystemen aus Sicht der Primar̈erzeuger - Ulrich Enneking; Thomas Obersojer; Marion Kratzmair (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2007)
– In order to ensure and to improve quality in the agro-food sector quality systems have to undergo a permanent change: simple end-of-the-pipe monitoring is therefore being replaced with management oriented concepts. Farmers are also increasingly requested to implement quality systems. This paper gives an overview of quality regimes in the agro-food sector and compares three systems in the domains of pork production, potato growing and the cultivation of hop. 315 Bavarian farmers were interviewed in order to identify factors which may influence the satisfaction with quality systems. Differences between the three quality regimes were moderate with respect to the overall satisfaction. Hop growers judged their system to improve production efficiency while the others did not to this extent. Socio-demographic factors do not have any significant impact on farmers' satisfaction with the quality systems. Key factors are gains in image, in sales and in production efficiency. The results of this study helps for a successful development of the plenty quality systems actually offered.
Keywords: 330; Qualitätsmanagement; Landwirtschaft; Ernährungsindustrie; Deutschland